Economic Feasibility for Recycling of Waste Crystalline Silicon Photovoltaic Modules. (27th June 2017) - D'Adamo, Idiano; Miliacca, Michela; Rosa, Paolo
Abstract : Cumulative photovoltaic (PV) power installed in 2016 was equal to 305 GW. Five countries (China, Japan, Germany, the USA, and Italy) shared about 70% of the global power. End-of-life (EoL) management of waste PV modules requires alternative strategies than landfill, and recycling is a valid option. Technological solutions are already available in the market and environmental benefits are highlighted by the literature, while economic advantages are not well defined. The aim of this paper is investigating the financial feasibility of crystalline silicon (Si) PV module-recycling processes. Two well-known indicators are proposed for a reference 2000 tons plant: net present value (NPV) and discounted payback period (DPBT). NPV/size is equal to −0.84 €/kg in a baseline scenario. Furthermore, a sensitivity analysis is conducted, in order to improve the solidity of the obtained results. NPV/size varies from −1.19 €/kg to −0.50 €/kg. The absence of valuable materials plays a key role, and process costs are the main critical variables.